2013
DOI: 10.1007/s10637-013-9992-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced folate carrier (RFC) as a predictive marker for response to pemetrexed in advanced non-small cell lung cancer (NSCLC)

Abstract: These results suggest the possible relation between RFC expression and response to treatment with antifolates (pemetrexed) independently of the tumor histology. Further studies are required to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The role of RFC transport in MTX antitumor activity has been extensively documented (14, 4648). In non–small cell lung cancer and malignant pleural mesothelioma, expression of RFC was also associated with clinical responses to treatment with PMX (49, 50), although in another study of malignant pleural mesothelioma an important role for PCFT in PMX clinical efficacy was strongly implied (51). Transport of cytotoxic antifolates by RFC into normal tissues is causal to toxicity since RFC is expressed in normal tissues as well as tumors (14).…”
Section: Discussionmentioning
confidence: 99%
“…The role of RFC transport in MTX antitumor activity has been extensively documented (14, 4648). In non–small cell lung cancer and malignant pleural mesothelioma, expression of RFC was also associated with clinical responses to treatment with PMX (49, 50), although in another study of malignant pleural mesothelioma an important role for PCFT in PMX clinical efficacy was strongly implied (51). Transport of cytotoxic antifolates by RFC into normal tissues is causal to toxicity since RFC is expressed in normal tissues as well as tumors (14).…”
Section: Discussionmentioning
confidence: 99%
“…RFC is a member of the solute carrier family and plays an important role in the uptake of FA [12]. RFC is the major transport system in cells for folate cofactors and antifolate therapeutics [34]. Studies have shown that inactivation of RFC leads to severe folate deficiency in the body [35].…”
Section: Discussionmentioning
confidence: 99%